Cost Analysis of Parturition with Sectio Caesarea at PKU Muhammadiyah Yogyakarta, Indonesia Hospital Based on INA-CBG’s Tariff in 2023 - Hadning, Ingenida; Yumna, Nurina Faridah; Viviandhari, Daniek; Taufani, Indra Putra; Ha, Hai-Anh (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2025)
The 2018 Riskesdas results showed that the prevalence of delivery by sectio caesarea in DIY was 23.1%. The high cost of sectio caesarea hinders access to public health, so the government implemented the INA-CBG's tariff. This study is the first to evaluate the INA-CBG's tariff based on the Permenkes RI Number 3 of 2023 for inpatient sectio caesarea delivery. This study aims to determine the difference between the cost of sectio caesarea delivery and the INA-CBG's tariff based on Permenkes RI Number 3 of 2023. Through this research, hospitals are expected to evaluate their services so that the costs of cesarean sections are under the INA-CBG's tariff. In addition, this research can serve as an evaluation of the INA-CBG's tariff for the government. This study used observational research methods and a cross-sectional approach. Data were obtained retrospectively by tracing medical records and treatment cost data of sectio caesarea patients from January to September 2023. Data were analyzed by descriptive analysis, one-sample t-test and one-sample Wilcoxon methods. The results of this study showed that the average actual cost was greater than the INA-CBG's rate, with significant differences in patients with class I code O-6-10-I, class II codes O-6-10-I and O-6-10-II, and class III code O-6-10-II, so that PKU Muhammadiyah Yogyakarta Hospital suffered losses.